THE IMPORTANCE OF ENGLISH LANGUAGE IN RAILWAY LOGISTICS EDUCATION: THE CASE OF KOKAND RAILWAY TECHNICAL COLLEGE - Asatillayeva Sehriyo Karimjon qizi, (TADQIQOTLAR, 2026)
Annotation:  In  the  context  of  globalization,  logistics  and  railway  transport require specialists who are able to communicate effectively at the international level. English has become the main language of professional interaction in logistics, transport documentation, and international cooperation. This article examines the importance of English  language  teaching  in  railway  logistics  education  with  special  reference  to Kokand Railway Technical College. The study focuses on the role of English lessons, teaching  styles,  learning  environment,  and  professional  orientation  of  language instruction.  Particular  attention  is  paid  to  the  integration  of  English  for  Specific Purposes (ESP) into the curriculum and the future development of students’ English competence.  The  findings  indicate  that  professionally  oriented  English  instruction significantly enhances students’ readiness for work in the international logistics sector.